Sequential analysis of δ15N in guard hair suggests late gestation is the most critical period for muskox calf recruitment. (17th January 2023) - Schmidt, Niels Martin; Michelsen, Anders; Hansen, Lars Holst; Aggerbeck, Marie Rønne; Stelvig, Mikkel; Kutz, Susan; Mosbacher, Jesper Bruun
Abstract : Rationale: Analysis of stable isotopes in tissue and excreta may provide information about animal diets and their nutritional state. As body condition may have a major influence on reproduction, linking stable isotope values to animal demographic rates may help unravel the drivers behind animal population dynamics. Methods: We performed sequential analysis of δ 15 N values in guard hair from 21 muskoxen ( Ovibos moschatus ) from Zackenberg in high arctic Greenland. We were able to reconstruct the dietary history for the population over a 5‐year period with contrasting environmental conditions. We examined the linkage between guard hair δ 15 N values in 12 three‐month periods and muskox calf recruitment to detect critical periods for muskox reproduction. Finally, we conducted similar analyses of the correlation between environmental conditions (snow depth and air temperature) and calf recruitment. Results: δ 15 N values exhibited a clear seasonal pattern with high levels in summer and low levels in winter. However, large inter‐annual variation was found in winter values, suggesting varying levels of catabolism depending on snow conditions. In particular δ 15 N values during January–March were linked to muskox recruitment rates, with higher values coinciding with lower calf recruitment. δ 15 N values were a better predictor of muskox recruitment rates than environmental conditions. Conclusions: Although environmental conditions may ultimately determine the dietary δ 15 N signal in muskox guard hairs, muskox calf recruitment was more strongly correlated with δ 15 N values than ambient snow and temperature. The period January–March, corresponding to late gestation, appears particularly critical for muskox reproduction.